Attachment style impacts behavior and early oculomotor response to positive, but not negative, pictures. Issue 3 (18th February 2015) - Silva, Catarina; Chaminade, Thierry; David, Da Fonseca; Santos, Andreia; Esteves, Francisco; Soares, Isabel; Deruelle, Christine
<x xml:space="preserve">Abstract</x> The present study investigated whether oculomotor behavior is influenced by attachment styles. The Relationship Scales Questionnaire was used to assess attachment styles of forty‐eight voluntary university students and to classify them into attachment groups (secure, preoccupied, fearful, and dismissing). Eye‐tracking was recorded while participants engaged in a 3‐seconds free visual exploration of stimuli presenting either a positive or a negative picture together with a neutral picture, all depicting social interactions. The task consisted in identifying whether the two pictures depicted the same emotion. Results showed that the processing of negative pictures was impermeable to attachment style, while the processing of positive pictures was significantly influenced by individual differences in insecure attachment. The groups highly avoidant regarding to attachment (dismissing and fearful) showed reduced accuracy, suggesting a higher threshold for recognizing positive emotions compared to the secure group. The groups with higher attachment anxiety (preoccupied and fearful) showed differences in automatic capture of attention, in particular an increased delay preceding the first fixation to a picture of positive emotional valence. Despite lenient statistical thresholds induced by the limited sample size of some groups (p < 0.05 uncorrected for multiple comparisons), the current findings suggest that the processing of positive emotions is affected by attachment styles. These results are discussed within a broader evolutionary framework.